ANALISIS PERILAKU KEJENUHAN BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DAN IMPLIKASINYA TERHADAP LAYANAN BK: STUDI KASUS DI SMP NEGERI 19 PADANG - Oviani, Eka; Netrawati, Netrawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Learning saturation is one of the problems that is often faced by students, especially in subjects that are considered difficult, such as Mathematics. At SMP Negeri 19 Padang, many students complained of boredom in Mathematics lessons, allegedly caused by the lack of student involvement in learning. This saturation can affect students' motivation and learning achievement, ultimately impacting the quality of education. This study aims to analyze students' learning saturation behaviour in mathematics subjects and its implications for Guidance and Counseling (BK) services. Using a descriptive quantitative approach, the study was conducted on 58 grade IX students of SMP Negeri 19 Padang who were selected through purposive sampling. Data were collected using a questionnaire with a Likert scale that measures four aspects of learning saturation: physical, emotional, motivational, and mental fatigue. The study results showed that 57% of students experienced moderate learning saturation and 23% at high to very high levels. The analysis revealed that motivational fatigue was the most serious problem, with 55% of students being at high to very high levels, followed by emotional fatigue (33%), mental fatigue (38%), and physical fatigue (19%). These findings have implications for developing a comprehensive BK program, including information services, group guidance, and individual counselling to help students overcome math learning boredom.Keywords: Learning Saturation, Mathematics, Counseling Guidance, Junior High School Students.